Are Vegetable Seed Oils Fueling the Obesity Epidemic? - Tyler Ransom (Institute of Labor Economics (IZA), 2024)
I argue that increased consumption of vegetable seed oils high in omega-6 polyunsaturated fats has driven obesity in the United States, a link overlooked in the economics literature. Obesity rates have closely tracked the level of seed oils in the food supply since 1960, while diverging from calorie intake and exercise trends post-2000. I present evidence from biochemistry supporting this hypothesis, demonstrating how seed oils disrupt metabolism, fat storage, and other biochemical processes. I document supporting evidence of these mechanisms in economics research and population health trends. I then develop a conceptual theory of imperfect information to explain consumer overconsumption of these oils, considering the interactions among food and drug companies, scientists, government regulators, and medical providers in shaping dietary information and the overall food supply. Finally, I discuss policy implications, emphasizing the need for a coordinated approach.
Keywords: I12; Q18; L66; I18; D72; 330; obesity; vegetable oils; seed oils; food policy; nutritional biochemistry; polyunsaturated fatty acids; political economy